A Contrastive View of Spatial Deixis in Croatian and English - Žic Fuchs, Milena (Array, 1994)
The paper aims at showing and explaining changes in paradigms reflecting spatial deixis in Croatian. The changes are explained as being grounded in conceptual changes reflecting the distinctions between urban and rural environments.